(untitled) (International Journal of Engineering and Computer Science, 2017)
The issue of Security is very paramount in any organization. Most security systems have a variety of components which can include finger print scanners, retina scan, rfid tag detectors as well as a keypad that allows users to input pins to gain access. These components can either be hardwired, which requires a contractor to drill and run wires throughout the house, or wireless, which allows for easy installation and replacement. And among them face recognition is the one which is attracting a lot of attention in society of security access. Few confidential Areas like bank vaults, critical server locations etc. need to be secured, and is possible through facial recognition system. In this paper an explanation on creating a low-cost stand-alone device is showcased using Facial Recognition technology to process and identify authorized personnel. The project is developed using Microsoft’s cognitive service. The implementation of the project is done using Raspberry Pi.